A Study Of Brand Management At Public Bank Berhad - Peng, Lean Boon (2009)
The case study seeks to identify/investigate/understand the brand management of Public Bank Berhad. This case study will also cover the strategies/measures taken by rival local banks in enhancing their already established bank brands. For the purpose of this case study, four local banks are selected to be the subjects of comparison.